2017
DOI: 10.1049/iet-gtd.2016.2041
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic synchrophasor estimation by Taylor–Prony method in harmonic and non‐harmonic conditions

Abstract: Dynamic phasor is suitable for analysis of non-stationary signals (such as power swings) in phasor measurement unit. In this study, dynamic phasor of the generated signals during power swing is analysed by a classical signal processing technique known as Prony. The Prony analysis is a useful technique to model a linear sum of damped complex exponential signals. In this study, a combination of the least square-based Prony analysis and Taylor expansion called as Taylor-Prony is proposed to estimate the dynamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…where and are real and estimated values. Figure 2 shows the total vector error of the proposed method in the first ten cycles; one cycle time delay of estimated phasor is compensated as in [27]. It can be concluded that the error occurring is above all the results of the introduced delay, similar to that of [15,21].…”
Section: Simulation Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…where and are real and estimated values. Figure 2 shows the total vector error of the proposed method in the first ten cycles; one cycle time delay of estimated phasor is compensated as in [27]. It can be concluded that the error occurring is above all the results of the introduced delay, similar to that of [15,21].…”
Section: Simulation Resultsmentioning
confidence: 68%
“…Figures 1(a) and 1(b) show the size of the estimated amplitude and phase of the fundamental dynamic phasor, using the proposed estimation method. It is clear that the main difference between the proposed method and some other methods based on the application of the least square methods [15,21,27], and the methods based on the application of Kalman filters [16,17,23,31] is in the occurrence of the delay in the estimation due to the use of the data window.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, several researches have successfully shown that the frequency assessment technology was able to detect the PQs of defects in power system. These technologies include Zero-crossing Algorithm [5][6][7], Discrete Fourier Transform (DFT) [8][9][10][11][12][13], Kalman Filter (KF) [14,15], Phase-Locked Loops (PLL) [16,17], Newton Algorithm [18,19], Least squares Algorithm (LMS) [20,21], Prony Algorithm [4,22], Taylor Algorithm [23,24], and Artificial-intelligence Algorithm [25,26].…”
Section: Introductionmentioning
confidence: 99%